Exploring the Genomic Traits of Non-toxigenic Vibrio parahaemolyticus Strains Isolated in Southern Chile - Castillo, Daniel; Pérez-Reytor, Diliana; Plaza, Nicolás; Ramírez-Araya, Sebastián; Blondel, Carlos J.; Corsini, Gino; Bastías, Roberto; Loyola, David E.; Jaña, Víctor; Pavez, Leonardo; García, Katherine (Frontiers in Microbiology, 2018)
Vibrio parahaemolyticus is the leading cause of seafood-borne gastroenteritis worldwide. As reported in other countries, after the rise and fall of the pandemic strain in Chile other post-pandemic strains have been associated with clinical cases, including strains lacking the major toxins TDH and TRH. Since the presence or absence of tdh and trh genes has been used for diagnostic purposes and as a proxy of the virulence of V. parahaemolyticus isolates, the understanding of virulence in V. parahaemolyticus strains lacking toxins is essential to detect these strains present in water and marine products to avoid possible food-borne infection. In this study we characterized the genome of four environmental and two clinical non-toxigenic strains (tdh-, trh- and T3SS2-). Using whole-genome sequencing, phylogenetic and comparative genome analysis we identified the core and pan-genome of V. parahaemolyticus of strains of southern Chile. The phylogenetic tree based on the core genome showed low genetic diversity but the analysis of the pan-genome revealed that all strains harbored genomic islands carrying diverse virulence and fitness factors or prophage-like elements that encode toxins like Zot and RTX. Interestingly, the three strains carrying Zot-like toxin have a different sequence, although the alignment showed some conserved areas with the zot sequence found in V. cholerae. In addition we identified an unexpected diversity in the genetic architecture of the T3SS1 gene cluster and the presence of the T3SS2 gene cluster in a non-pandemic environmental strain. Our study sheds light on the diversity of V. parahaemolyticus strains from the southern Pacific which increases our current knowledge regarding the global diversity of this organism.